Peran Bank Syariah Indonesia (BSI) KCP Cirebon Sisingamangaraja Terhadap Perkembangan Sektor UMKM - Ghoni, Abdul; Ramadhan, Eep Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
MSME financing makes a major contribution to improving the performance of Islamic banks. The role of MSME financing is in accordance with the main role of Islamic banks as financial intermediary institutions, collecting funds from the public and channeling them in the form of financing. As in the case of the BSI KCP Sisingamangaraja Cirebon, it has carried out its duties as a collector of public funds and a distributor of funds, which of course will be channeled back to the community. It can be in the form of KPR, Mitra Guna, Gold Installments or other financing such as KUR and Non-KUR. The purpose of this study is to analyze the role of Bank Syariah Indonesia KCP Sisingamangaraja Cirebon in contributing to developing the MSME sector by helping to provide capital to customers who want to develop their business in the MSME sector, as well as what forms of education and motivation have been provided by the BSI KCP Sisingamangaraja Cirebon for MSME customers to get support so they can develop their business to the fullest. The type of research conducted by the author is field research using qualitative methods, while the research data collection techniques are collected through interviews, observation, documentation, books, journal articles and then analyzed using descriptive methods. The results of the research analysis carried out are in accordance with the formulation of the problem, namely: (1) The role of BSI KCP Sisingamangaraja related to capital assistance has several stages, namely: The stage of collecting documents, validation, financing process, field surveys, committees, contracts, disbursement, maintenance and repayment. (2) The role of BSI KCP Sisingamangaraja Cirebon related to education and motivation for MSMEs has not run optimally. BSI KCP Sisingamangaraja Cirebon has so far not held an MSME development program to educate how important and potential it is to develop MSME. Then, BSI KCP Sisingamangaraja Cirebon has so far not held training and digitization for MSME actors as a form of motivation provided by BSI.